2021
DOI: 10.1016/s2468-2667(21)00012-8
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 vaccine hesitancy in a representative working-age population in France: a survey experiment based on vaccine characteristics

Abstract: Background Opinion polls on vaccination intentions suggest that COVID-19 vaccine hesitancy is increasing worldwide; however, the usefulness of opinion polls to prepare mass vaccination campaigns for specific new vaccines and to estimate acceptance in a country's population is limited. We therefore aimed to assess the effects of vaccine characteristics, information on herd immunity, and general practitioner (GP) recommendation on vaccine hesitancy in a representative working-age population in France. MethodsIn … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

111
534
12
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 661 publications
(729 citation statements)
references
References 27 publications
111
534
12
9
Order By: Relevance
“…Since the DHPSP account exclusively posts science-based content, it is reasonable to assume that it attracted followers with interests in science. This assumption is in line with a recent study by Schwarzinger et al [38], which revealed that COVID-19 vaccination hesitancy was highly prevalent among people with low educational levels in the French population. These findings are in line with other, more recent studies that were conducted in France, the United States of America, and Australia [39][40][41].…”
Section: Discussionsupporting
confidence: 91%
“…Since the DHPSP account exclusively posts science-based content, it is reasonable to assume that it attracted followers with interests in science. This assumption is in line with a recent study by Schwarzinger et al [38], which revealed that COVID-19 vaccination hesitancy was highly prevalent among people with low educational levels in the French population. These findings are in line with other, more recent studies that were conducted in France, the United States of America, and Australia [39][40][41].…”
Section: Discussionsupporting
confidence: 91%
“…an der Heiden and Hamouda 2020). But how many people an infected individual will indeed contaminate will depend, for example, on the number of people an infected person is exposed to on each of those days, on the probability of each exposure becoming an infection, on the duration of infectiousness including periods of asymptomatic infectiousness, and other individual characteristics such as age and obesity (Edwards et al 2021, Pandit 2020). Hence the reproduction number is an average number that assumes away a number of supposedly important, and possibly time-varying, characteristics that may affect the "reproduction" of the virus depending on who, when and where one is infected.…”
Section: Acceleration and Deceleration Of Harmmentioning
confidence: 99%
“…Even if a vaccination campaign is under way, testing will continue to be important as long as herd immunity will not be attained. Given virus mutations and vaccine hesitancy, there may still a long shot to go until worldwide immunity will be obtained (Schwarzinger et al 2021). Massive and continuous low-threshold testing (in addition to other policies such as respecting social distancing rules or face masks for example) provides the possibility for an open society.…”
Section: Testing Strategiesmentioning
confidence: 99%
“…On the other hand, strongly hesitant people also include anti-vaxxers, who have been found to be insensitive to communication about both individual and collective benefits of COVID-19 vaccination. 8 Accordingly, these people (ie, those who say they will never get vaccinated) are likely to remain insensitive to any additional arguments on the benefits of vaccination.…”
mentioning
confidence: 99%
“…In countries with a similarly rapid and successful vaccination campaign as the UK's (eg, the USA and Israel, in which 46% and 63% of the general population, respectively, had received at least one COVID-19 vaccine dose by May 9, 2021), 5 COVID-19 vaccination is becoming the social norm, and a large proportion of strongly hesitant people who have postponed their decision might be further convinced by a positive reinforcement from official communication about vaccination. In countries with early reluctance about COVID-19 vaccination, 8 distrust in information from official sources, 9 and slow growth of vaccination coverage (eg, only 26% of the French population had received a vaccine dose by May 8, 2021), 5 a large proportion of strongly hesitant people might be anti-vaxxers and reinforcing the official communication about vaccination might not only be ineffective but even counterproductive. 10 Additional input from social sciences are urgently needed in these country settings if the ultimate goal is to reach herd immunity by mass vaccination.…”
mentioning
confidence: 99%